2020
DOI: 10.21786/bbrc/13.7/24
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Luxators in Dental Extraction Among Dentists

Abstract: Luxator looks like an elevator, but the tip of the instrument is significantly thinner and somewhat flatter than an elevator.One of the frequently occurring frustrating challenges when extracting teeth is breaking the tooth off at the bone level, or extracting a tooth that has decayed off at the bone level.The aim of this study is to determine the level of knowledge about the usage of luxator in dental extraction by the dentist and getting to the how aware they are about the use of luxator in their practice .T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Although the staggered approach may allow for scaffolding of the procedure and a subsequent reduction in the stress and anxiety experienced by students (quotation on Table 4 ) in the three-and-a-half-day course, the course coordinator may have to consider extending the duration of the course and amend the outcomes of the course to include elevators/luxators for the intra-alveolar (simple tooth extraction) procedure. The combination of forceps and elevators/luxators could potentially result in a less traumatic extraction with less bone and soft tissue destruction [ 46 ]. A recent study at a UK dental school reported the use of instructional videos for increasing self-confidence of dental students with luxator use [ 45 ].…”
Section: Summary and Discussion Of The Findingsmentioning
confidence: 99%
“…Although the staggered approach may allow for scaffolding of the procedure and a subsequent reduction in the stress and anxiety experienced by students (quotation on Table 4 ) in the three-and-a-half-day course, the course coordinator may have to consider extending the duration of the course and amend the outcomes of the course to include elevators/luxators for the intra-alveolar (simple tooth extraction) procedure. The combination of forceps and elevators/luxators could potentially result in a less traumatic extraction with less bone and soft tissue destruction [ 46 ]. A recent study at a UK dental school reported the use of instructional videos for increasing self-confidence of dental students with luxator use [ 45 ].…”
Section: Summary and Discussion Of The Findingsmentioning
confidence: 99%